Analysis of Flood Susceptibility in Pati Regency Using Geographic Information Systems (GIS) and Analytical Hierarchy Process (AHP) - Restianto, Mohammad Obie; Poniman, Aris; Supriyatno, Makmur (CV. AFDIFAL MAJU BERKAH, 2024)
Floods are disasters that often occur in Indonesia. Society and the environment feel the negative impacts of flooding. Floods are ranked as the second most frequent disaster in Indonesia according to the Indonesian Disaster Information Data (DIBI) from the National Disaster Management Agency (BNPB). This research aims to conduct a flood susceptibility analysis in Pati Regency. The method used in this research is Analytical Hierarchy Process (AHP) combined with Geographic Information Systems (GIS). This research uses ten factors that influence flood susceptibility, there are Topographic Wetness Index (TWI), Elevation, Slope, Precipitation, Land Use and Land Cover (LULC), Normalized Difference Vegetation Index (NDVI), Distance from Rivers, Distance from Roads, Drainage Density, and Soil Type. The results of this research show that there are four levels of flood susceptibility in Pati Regency, there are low level reaching 3.47%, moderate level reaching 64.85%, high level reaching 31.62%, and very high level reaching 0.07%.